الآليات الوقائية لتنفيذ قواعد القانون الدولي الإنساني - دليلة زيغمي (My University, 2025)
Abstract To ensure the implementation of International Humanitarian Law (IHL), a series of preventive mechanisms—both international and domestic—have been established. Their purpose is to secure comprehensive protection, by the international community, of persons and property entitled to protection, in accordance with the rules objectively laid down by the Geneva Conventions and their two Additional Protocols. The application of these rules is not confined to periods of armed conflict but also extends into peacetime. The international preventive framework comprises institutions that ensure, on the ground, the enforcement of IHL provisions and norms. On one hand, they promote respect for these rules and facilitate humanitarian relief through the Protecting Power and its alternatives—principally the International Committee of the Red Cross (ICRC). On the other, they include mechanisms designed to curb violations of IHL by conducting investigations and issuing recommendations, notably the International Humanitarian Fact Finding Commission. Complementing these are domestic preventive measures, which encompass the obligation to respect humanitarian rules in both international and non international armed conflicts; the requirement to accede to IHL treaties; the incorporation and harmonization of humanitarian provisions and norms within national legislation; and the dissemination and promotion of IHL by qualified practitioners and advisors, all aimed at enhancing the effectiveness of its provisions and norms. ......................... الملخص لتحقيق تطبيق القانون الدولي الإنساني تم وضع آليات وقائية دولية وداخلية، تهدف إلى تفعيل حماية شاملة من المجتمع الدولي للأشخاص والممتلكات المشمولين بالحماية، وفقا لقواعد صاغتها بشكل موضوعي اتفاقيات جنيف وبروتوكوليها الإضافيين، واتخاذ هذه القواعد لا يقتصر تفعليها وقت النزاعات المسلحة، بل تمتد أعمالها كذلك إلى زمن السلم. فاتخاذ مجموعة الآليات الوقائية الدولية والتي هي عبارة عن مؤسسات، تضمن تنفيذ أحكام وقواعد القانون الدولي الإنساني، على أرض الواقع التي تعنى من جهة بالتوعية لاحترام هذه القواعد والإغاثة الإنسانية منها الدولة الحامية وبدائلها المتمثلة في أهمها اللجنة الدولية للصليب الأحمر، أو آليات تحد من هذه انتهاكات التي يتعرض لها القانون الدولي الإنساني بالتحقيق ووضع توصيات من جهة أخرى كاللجنة الدولية الإنسانية لتقصي الحقائق. إلى جانب ذلك وجود آليات داخلية وقائية منها ضرورة احترام القواعد الإنسانية المنظمة للنزاعات الدولية وغير الدولية، ووجوب الانضمام للاتفاقيات المتعلقة بالقانون الدولي الإنساني، وتضمين التشريعات الوطنية أحكام وقواعد إنسانية ومواءمتها لها، ونشر هذا القانون، والتعريف به من خلال المؤهلين والمستشارين لجعل أحكامه وقواعده أكثر فعالية. .............................. Résumé Pour assurer la mise en œuvre du droit international humanitaire, des mécanismes de prévention internationaux et nationaux ont été mis en place, visant à activer la protection intégrale par la communauté internationale des personnes et des biens protégés, conformément aux règles formulées objectivement par les Conventions de Genève et leurs Protocoles additionnels. L’application de ces règles ne se limite pas aux périodes de conflit armé, mais s’étend également au temps de paix. L'adoption d'un ensemble de mécanismes internationaux de prévention, qui sont des institutions qui garantissent la mise en œuvre des dispositions et des règles du droit international humanitaire sur le terrain, qui se préoccupent, d'une part, de sensibiliser au respect de ces règles et de l'aide humanitaire, y compris l'État protecteur et ses alternatives, dont le plus important est le Comité international de la Croix-Rouge, ou des mécanismes qui limitent ces violations auxquelles le droit international humanitaire est exposé en enquêtant et en faisant des recommandations, d'autre part, comme la Commission internationale humanitaire d'établissement des faits. En outre, il existe des mécanismes de prévention internes, notamment la nécessité de respecter les règles humanitaires régissant les conflits internationaux et non internationaux, l'obligation d'adhérer aux accords relatifs au droit international humanitaire, l'inclusion de dispositions et de règles humanitaires dans la législation nationale et leur harmonisation avec elles, ainsi que la diffusion de ce droit et sa diffusion par l'intermédiaire d'experts et de consultants qualifiés pour rendre ses dispositions et ses règles plus efficaces.
Keywords: Keywords: International Humanitarian Law; preventive mechanisms; national; international; Protecting Power; International Committee of the Red Cross; International Humanitarian Fact Finding Commission; accession; harmonization; dissemination; training.; الكلمات المفتاحية: القانون الدولي الإنساني، آليات، وطنية، دولية، وقائية، الدولة الحامية، اللجنة الدولية للصليب الأحمر، اللجنة الدولية الإنسانية لتقصي الحقائق، الانضمام، الموائمة، النشر، التأهيل.; Mots-clés: Droit international humanitaire; mécanismes; préventif; puissance protectrice; Comité international de la Croix-Rouge; Commission internationale humanitaire d'établissement des faits; adhésion; harmonisation; diffusion; qualification.